Strategi Promosi Kesehatan Menghadapi Dampak Penggunaan Gadget pada Perkembangan Bahasa Bicara Anak - Ruth Evita Gloria Lbn Gaol; Nur Alam Fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication through technology such as gadgets has become a necessity to support daily life activities. Not only for adults, but gadgets have also entered young children. Excessive use of gadgets in early childhood will indirectly affect various ongoing ability developments in early childhood. Children who spend too much time with gadgets will have less time for social interaction with the people around them, and children will receive less stimulation during social interactions. Stimulation is really needed in early childhood to encourage the development of children's abilities, especially spoken language abilities which develop very rapidly in early childhood. If a child does not receive enough supportive stimulation, the risk of the child experiencing speech language delays is greater. So a health promotion strategy is needed to support children in achieving developmental milestones well, through the involvement and active role of parents or caregivers during this period.